Intracoronary artery retrograde thrombolysis for ST-segment elevation myocardial infarction with a tortuous coronary artery: A case report and review of the literature - Shen, Mingzhi; Lu, Haihui; Liao, Yichao; Wang, Jian; Guo, Yi; Zhou, Xinger; Nong, Yingqiao; Fu, Zhenhong; Wang, Jihang; Guo, Yuting; Zhao, Shihao; Fan, Li; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background How to deal with large thrombus burdens of culprit’s blood vessel remains a great challenge in the treatment of acute myocardial infarction. Case presentation A 32-year-old Chinese man was diagnosed with ST-segment elevation myocardial infarction (STEMI). Coronary angiography revealed that the distal end of a tortuous left circumflex was completely occluded by a large amount of thrombus. Cutted balloon-directed intracoronary artery retrograde thrombolysis (ICART) with urokinase led to the restoration of coronary blood flow. Because there was no obvious plaque rupture or artery stenosis in the coronary artery, it was only dilated, and no stent was implanted. Conclusion Cutted balloon-directed ICART can be performed effectively and safely in some STEMI patients with tortuous coronary vessels and large thrombus. (REST or named ICART ClinicalTrials.gov number, ChiCTR1900023849).